Influential Safety Performance and Assessment in Construction Projects: A Review - Alaloul, W.S. (Springer, 2020)
In construction industry safety issues are the major concern for the stakeholders due to its hazardous nature as it causes injuries and losses of lives to workers. A lot of safety mitigations have been taken but still, the fatalities in construction projects are increasing day by day. The focus of this theoretical review is to underline the critical factors causing poor safety performance in construction projects. The review was carried out in two phases. In the first phase, critical factors causing poor safety performance were highlighted. Besides emphasizing the critical factors, other studies have been reviewed in the second phase where various methods and techniques have been highlighted as safety assessment tools to knob the accidents at the earliest stage of the project. The key findings of this review paper are the main critical factors which influence the construction safety and the developed techniques to enhance the project safety performance. By focusing on the issues and available solutions, stakeholders can bring betterment into their projects. Â© Springer Nature Switzerland AG 2020.